UPAYA MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN PPKN PADA MATERI POLA HIDUP GOTONG ROYONG MENGGUNAKAN MODEL PEMBELAJARAN TALKING STICK BERBANTUAN KARTU PINTAR KELAS IV DI SDN BENDO 2: PENELITIAN TINDAKAN KELAS - Diana Putri Rahmawati; Evanda Vella Delli; Nabila Syifa Ramadhani; Melik Budiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Many students do not interact, actively participate in the learning process and students do not concentrate when the teacher explains the material on the mutual cooperation lifestyle of PPKN lessons. This happened to fourth grade students of SDN Bendo 2, this has an impact on the PPKN subject scores on the Mutual Cooperation Lifestyle material, where around 57.14% of students are below the KKM score standard. This is because the learning model used by the teacher still uses a lecture approach and without learning media. One of the solution steps taken is to replace the learning model currently used with a Talking stick learning model assisted by smart cards. This study aims to determine the application of the Talking stick learning model, to determine the improvement in student learning outcomes in the PPKN subject on the mutual cooperation lifestyle material, and to increase the motivation of fourth grade students of SDN Bendo 2. The research model used is Classroom Action Research (CAR) with 1 cycle using the Talking stick model assisted by smart cards consisting of four steps, namely: planning, implementation, observation, and reflection. This research was applied to 14 fourth grade students. The learning outcomes of students obtained during the implementation of the action increased as seen from the results of cycle I as many as 14 students completed with an average score of 90.5 and a percentage of 100%. Based on the results of the study, it shows that the Talking stick model assisted by smart cards can improve learning outcomes, participation, and student learning motivation.